Exploring the Use of Artificial Intelligence as Writing Assistant in EFL Classroom: A Systematic Literature Review - Mulyana, Novita (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2025)
The rapid development of artificial intelligence has brought English language learning to a new era. English language skills are now can be acquired and enhanced with a support of artificial intelligence tools. This study aims to explore the implementation of artificial intelligence in English as Foreign Language (EFL) teaching and learning process especially in enhancing EFL students’ writing skill as well as to review its impact on EFL students. Systematic Literature Review approach was utilized with seventeen empirical research articles chosen as data source in this study. The selection of the data sources was conducted in two stages, namely based on title and based on full text. The articles were gathered from google scholar search engine using “AI for English writing EFL students” as the keywords. The result of the analysis shows that there are several types of AI-powered tools or application that can be used as writing assistant in EFL classroom. Those tools are, for instance, ChatGPT, Grammarly, Google Docs, Writerly, Quillbot, any some others. The implementation of AI-powered tools as writing assistant has proven to be able to improve EFL students’ writing skills, motivation, and perception. However, several drawbacks of the use of AI are also pointed out, such as concern on over-reliance and plagiarism issue. Therefore, it is essential to design a balance integration between the use of AI as writing assistant and conventional learning approach in an EFL classroom.